SAT0026 Differential levels of il-7 expression in adventitia of non-ra and ra patients with coronary artery disease. (12th June 2018) - Burska, A.N.; Sime, K.; Wiliams, A.; Mikkelsen, K.; Saatvedt, K.; Almdahl, S.M.; Risnes, I.; Goodyear, C.; Hollan, I.; Ponchel, F.
Abstract : Background: Rheumatoid Arthritis (RA) patients have increased cardiovascular risk due to accelerated atherosclerosis (ATS), which significantly contributes to excess mortality in RA 1 . The increased cardiovascular risk cannot be fully explained by traditional risk factors and systemic chronic inflammation appears to play a crucial role. Interestingly, IL-7, a proinflammatory cytokine involved in RA pathogenesis, appears to play a role also in atherosclerosis 2 but its effect on cardiovascular disease (CVD) in RA has not been studied yet. Objectives: To examine serum IL-7 levels and expression of IL-7, IL-7R, CD3 and CD20 in aortic adventitia of RA and non-RA patients with coronary artery disease (CAD) and to search for relationships between systemic IL-7 levels and expression of vascular markers, cardiovascular risk factors including metabolic and inflammatory markers. Methods: We examined 19 RA patients and 20 non-RA patients undergoing coronary artery bypass graft surgery included in the Feiring Heart Biopsy Study. Serum IL-7 levels were measured by chemiluminescence (MSD). Biopsies from the adventitia of thoracic aorta from a subset of patients (12 RA and 14 non-RA) were stained for IL-7, IL-7R, CD3 and CD20 by immunohistochemistry and scored per mm 2 of tissue. Results: Non-RA patients had lower IL-7 serum levels than RA (3.4±3.3 vs. 6.7±3.5, p<0.05). Independently of RA diagnosis, IL-7 significantly correlated with CRP (rho=0.450, p=0.008), triglycerides (TG, rho=0.566, p=0.005), glucose (rho=0.642, p=0.001) and hypertension (p=0.036). Levels of IL-7 were associated with New York Heart Association class (rho=0.429, p=0.014) and this was stronger in non-RA patients (rho=0.577, p=0.010). No associations were found with smoking or markers of CVD severity (i.e. numbers of arteries with significant stenosis or number of previous myocardial infarcts (MI)). The number of IL-7 +and IL-7R+cells/mm 2 in adventitia were significantly higher in RA (134.2±45.5 and 144±49.9 respectively) than non-RA patients (46.9±22.8 and 54.4±20.2, p<0.005) and were associated with serum IL-7 levels (rho=0.551 and rho=0.588, p<0.01). Both IL-7 +and IL7R+cells were associated with a positive history of MI (p=0.047 and p=0.005) and IL-7R+cells with the number of previous MIs (rho=0.408, p=0.038). Only in RA patients, IL-7R+cells showed a trend for correlation with TG (rho=0.771, p=0.072). IL-7 +and IL-7R+cells correlated with CD3 (rho=0.688, p=0.013 and rho=0.630 p=0.028), but no correlation was found with CD20. Cholesterol and HDL levels were associated with IL-7 +cells only in non-RA patients (rho=0.729 p=0.04 and rho=0.733, p=0.038). Conclusions: Among patients with CAD, those with RA had higher serum IL-7 and a greater expression of both IL-7/IL-7R is aortic adventitia. Systemic levels of IL-7 were related to its vascular expression. Thus, the IL-7/IL-7R axis may play a role in the accelerated atherogenesis observed in RA; further studies are needed to elucidate the precise role of IL-7 and impact of potential IL-7R blockade in CV risk in RA. References: [1] Kaplan MJ. Curr. Opin. Rheumatol2006;18(3):289–297. [2] Damås JK, et al. Circulation2003;107(21):2670–2676. Disclosure of Interest: None declared